Upholding Justice Surah An-Nisa Verse 135 (According to Sayyid Qutb and Quraish Shihab) - Andyaulya Fitra; Abdul Matin Bin Salman (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2024)
Justice is balance which not only includes a balance of rights and obligations, but also harmony with fellow humans. This research aims to reveal the concept of justice in Surah An-Nisa verse 135. The approach used is a qualitative approach with the type of library research, therefore the data and information obtained refer to various treasures related to the focus of writing, namely related with Justice. with the main source being the Koran, Sayyid Qutb's opinion in Tafsir Fi Dzilalil Quran and Quraish Shihab in Tafsir Al-Misbah. From other sources such as journal articles and the internet to obtain clarity regarding the concept of justice referred to in Surah An-Nisa Verse 135. Research Results Show Several important principles that can be found in Surah An-Nisa Verse 135 are First, be fair to everyone. Second, don't follow your desires. Third, believe that Allah is all-seeing, believe that every action will definitely be rewarded. Upholding Justice contained in Q.S. An-Nisa: 135 has a very comprehensive concept. Namely by collaborating three very important components in implementing it.